Performance of broilers submitted to high CO2 levels during incubation combined with temperature fluctuations at late post-hatch - Fernandes,JIM (2014)
Incubation represents around 1/3 of the life cycle of broilers of modern strains; therefore, the appropriate management of this period is crucial to ensure the quality of the neonate. An experiment evaluated the effect of carbon dioxide concentrations during incubation on the live performance, heart morphology, and differential leukocyte count in the blood of broilers submitted to fluctuating temperatures between 35 and 42 days of age. In total, 2,520 fertile eggs were distributed according to a completely randomized design with four CO2 concentrations (4,000; 6,000; 8,000 and 10,000 ppm) during the first ten days of incubation, after which all eggs were incubated at the same CO2 level (4,000 ppm). After hatching, male chicks were placed in the experimental broiler houses, and at 35 days of age, 25 birds from each level of CO2 were separated and placed in cages to study the effect of cyclic temperature variations up to 42 days of age on their live performance, heterophil:lymphocyte ratio, and heart morphology. At 42 days of age, blood was collected for hematology and two birds per replicate were sacrificed and evaluated for ascites score and heart and liver relative weights. Heart morphology was assessed by analyzing digital images. In this experiment, hypercapnia during incubation and fluctuating temperatures during the growout did not affect mortality, ascites score, heart and liver relative weights, or heart characteristics (p>0.05). However, heterophill:lymphocyte ratio increased (p<0.05) with increasing carbon dioxide concentrations during incubation. It was concluded that high CO2 levels during incubation did not influence the resistance of broilers to fluctuating temperatures during the last week of age.